2021
DOI: 10.1159/000521142
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries in Children with Attention Deficit/Hyperactivity Disorder: A Meta-Analysis

Abstract: Objectives: To evaluate whether children with attention deficit/hyperactivity disorder (ADHD) are more affected by dental caries than children without ADHD by means of a systematic review and meta-analysis. Design: Electronic searches was performed in four databases (PubMed, Embase, Scopus, and Web of Science) in July 2021. Grey literature search in OpenGrey, a search in Google Scholar, and searches in the reference list of included articles were also conducted. The eligibility criteria were observational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…In a study utilizing the International Caries Detection and Assessment System (ICDAS), it was revealed that children affected by ADHD had an elevated risk of developing dental caries in both their primary and permanent dentition [ 29 ]. A recent meta-analysis further supported these findings, indicating that children with ADHD were more susceptible to dental caries development compared to their healthy peers [ 30 ]. Similar outcomes were observed in the current study.…”
Section: Discussionmentioning
confidence: 84%
“…In a study utilizing the International Caries Detection and Assessment System (ICDAS), it was revealed that children affected by ADHD had an elevated risk of developing dental caries in both their primary and permanent dentition [ 29 ]. A recent meta-analysis further supported these findings, indicating that children with ADHD were more susceptible to dental caries development compared to their healthy peers [ 30 ]. Similar outcomes were observed in the current study.…”
Section: Discussionmentioning
confidence: 84%
“…There is evidence that these conditions can negatively affect oral health. Children with ADHD have higher prevalence of caries, 9 hyposalivation, 10 higher plaque index, 10 and gingival bleeding index 11 . The scope of practice of dentistry has been expanding in the recent years and orofacial pain has been recognised by the American Dental Association (ADA) as a new dental specialty 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies from diverse geographical regions have contributed to a growing body of evidence indicating that intellectually disabled individuals are at an elevated risk for dental caries due to a complex interplay of factors [1] [2].…”
Section: Introductionmentioning
confidence: 99%